Reframing Fatherlessness in the Digital Public Sphere: A Maqāṣid-Based Reconstruction through Qawā‘id Fiqhīyah - M. Sa’ad Alfanny; Ach Badri Amin; Ahmad Sholakhuddin Al Af Ghoni (Zamzami Scholar Publishing, 2026)
The phenomenon of fatherlessness has shifted from the domestic sphere to the digital public space, where social media serves as a medium for articulating personal experiences and fostering collective solidarity. This article analyzes this phenomenon through the lens of Qawā‘id Fiqhīyah to offer a normative framework that transcends the dominance of conventional psychological and sociological approaches. This study argues that the absence of the father’s role can be understood as a non-material social harm (ḍarar) that has an impact on the protection of the soul (ḥifẓ al-nafs) and reason (ḥifẓ al-‘aql). The results of the analysis show that applying the principles of al-ḍarar yuzāl and dar’ al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ confirms the urgency of mitigating and providing psychosocial support, including through digital platforms, as part of efforts to reduce harm. At the same time, the principle of al-‘ādah al-muḥakkamah provides legitimacy for the practice of digital solidarity as a form of contemporary social adaptation. However, this legitimacy remains limited by the principle of non-maleficence (lā ḍarar wa lā ḍirār) to prevent the commodification of trauma and the reproduction of new harm. This article concludes that Qawā‘id Fiqhīyah provides a contextual and comprehensive ethical framework for responding to family crises amid an ever-evolving digital ecosystem.